Asymptotic classification of aliasing structures. (1992) - Izmailov, R. N.; Pokrovskii, A. V.
Abstract : The effects of quantization of quickly oscillating functions are considered. An asymptotical classification of aliasing spots is considered. The results obtained may be used in the restoring of certain features of initial functions.